M6A Reader YTHDF1‐Targeting Engineered Small Extracellular Vesicles for Gastric Cancer Therapy via Epigenetic and Immune Regulation. Issue 8 (26th December 2022) - You, Qing; Wang, Fang; Du, Rong; Pi, Jingnan; Wang, Huayi; Huo, Yue; Liu, Jingyi; Wang, Chen; Yu, Jia; Yang, Yanlian; Zhu, Ling
Abstract: N 6 ‐methyladenosine (m 6 A) modulators decide the fate of m 6 A‐modified transcripts and drive cancer development. RNA interference targeting m 6 A modulators promise to be an emerging cancer therapy but is challenging due to its poor tumor targeting and high systematic toxicity. Here engineered small extracellular vesicles (sEVs) with high CD47 expression and cyclic arginine–glycine–aspartic (c(RGDyC)) modification are developed for effective delivery of short interfering RNA against m 6 A reader YTH N6‐methyladenosine RNA binding protein 1 (YTHDF1) to treat gastric cancer via epigenetic and immune regulation. This nanosystem efficiently depletes YTHDF1 expression and suppresses gastric cancer progression and metastasis through hampering frizzled7 translation and inactivating Wnt/β‐catenin pathway in an m 6 A dependent manner. Loss of YTHDF1 mediates overexpression of interferon (IFN)‐γ receptor 1 and enhances IFN‐γ response, promoting expression of major histocompatibility complex class I on tumor cells to achieve self‐presentation of the immunogenic tumor cells to stimulate strong cytotoxic T lymphocytes responses. CD47 expression on the engineered sEVs can competitively bind with signal regulatory protein α to enhance phagocytosis of the tumor cells by tumor‐associated macrophages. This versatile nanoplatform provides an efficient and low toxic strategy to inhibit epigenetic regulators and holds great potential in promoting immunotherapy. Abstract : The m 6 A reader YTH N6‐methyladenosine RNA binding protein 1 (YTHDF1)‐targeting engineered small extracellular vesicles (sEVs) inhibit gastric tumor progression and metastasis through epigenetic and immune regulation. The engineered sEVs hamper frizzled7 translation and inactivate Wnt/β‐catenin pathway in an m 6 A dependent manner, and promote immunotherapy by direct self‐presentation of immunogenic tumor and CD47 blockade‐based immunosuppression reversal.